Challenges and opportunities regarding the COVID-19 pandemic on urban mobility in Constanta, Romania - Stan, Mari-Isabella; Tasențe, Tănase; Rus, Mihaela (Technium Social Sciences Journal, 2023)
The global COVID-19 pandemic has had a significant impact on urban mobility in Constanta, Romania and other cities around the world. This has resulted in reduced travel, increased bicycle and pedestrian trips, fewer taxicabs, and shorter public transport hours. It has also generated increased challenges for local authorities regarding safety, hygiene, air quality, road network management and public trust in public transit systems. On the other hand, the pandemic presents many opportunities for cities to rethink their urban mobility plans and adopt more sustainable transport solutions. This paper will look at the challenges and opportunities posed by the pandemic on urban mobility in Constanta and the measures that can be taken to mitigate the negative impacts while taking advantage of the opportunities it provides. This paper aims to provide an overview of the perception of urban mobility in the city of Constanța, Romania. It draws upon the results of a survey conducted among citizens in the city, which asked respondents to assess their perception regarding the quality, availability, and efficiency of urban mobility services in their area. The results show that most respondents feel that the availability of urban mobility services is limited and that the quality and efficiency of these services are poor. Additionally, majority of respondents feel that the lack of public transportation options and the lack of bicycle lanes impede urban mobility in Constanța. The paper concludes by suggesting that the city should consider investing in improved public transportation options and bike lanes in order to increase its urban mobility. Additionally, public education surrounding urban mobility and transportation safety is recommended.